Non-Supersymmetric CS-Matter Theories with Known AdS Duals - Davide Forcella; Alberto Zaffaroni (Advances in High Energy Physics)
We consider three-dimensional conformal field theories living on a stack of N anti-M2 branes at the tip of eight-dimensional supersymmetric cones. The corresponding supergravity solution is obtained by changing sign to the four-form in the Freund-Rubin solution representing M2 branes (“skew-whiffing” transformation) and it is known to be stable. The existence of these non-supersymmetric, stable field theories, at least in the large N limit, is a peculiarity of the